FIELD TEST RESULTS OF MACHINE SOFTENERS THAT LAY FILM TOGETHER WITH SOIL PREPARATION FOR SOWING MELON CROPS - Gulomov Laziz Khudayberdiyevich (The Conference Hub, 2025)
The article describes a new technology of soil cultivation and preparation for planting melon crops, which involves the simultaneous implementation of technological processes such as soil cultivation without a tiller, loosening the subsoil along the seeding line, and preparing the soil for planting. The structure, principle of operation, and field test results of the improved unit implementing the new technology are presented.
Keywords: melon crops, soil, body, softener, planting, film, productivity, chiseling.